2017
DOI: 10.1016/j.jaad.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atopic dermatitis on health-related quality of life and productivity in adults in the United States: An analysis using the National Health and Wellness Survey

Abstract: AD is associated with a substantial humanistic burden that is similar in magnitude to that of psoriasis, which is also recognized for its debilitating symptoms, indicating the need for more effective treatments for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 25 publications
11
145
2
Order By: Relevance
“…As expected, the work impairment was lowest in the participants with mild AD. This is in line with previous reports based on data from the 2013 U.S. NHWS, where respondents with moderate‐to‐severe AD generally showed a higher disease burden than respondents with mild AD . This is now also shown to be consistent across regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, the work impairment was lowest in the participants with mild AD. This is in line with previous reports based on data from the 2013 U.S. NHWS, where respondents with moderate‐to‐severe AD generally showed a higher disease burden than respondents with mild AD . This is now also shown to be consistent across regions.…”
Section: Discussionsupporting
confidence: 91%
“…Being a chronically relapsing condition, AD is associated with a high disease burden, with a significant physical and social impact. AD has been reported to have a detrimental effect on health‐related quality of life, including aspects such as sleep disturbance and reductions in work productivity . However, the burden of AD in adult patients has still not been well characterized .…”
mentioning
confidence: 99%
“…A systematic review revealed an association between autism spectrum disorders and AD, even though the authors stated somewhat inconsistent results due to variability in the study population and design, and the presence of other risk factors acting as confounding factors [30]. An increased risk of depression has been noted in both adolescents and adults affected with AD [23, 31]. AD patients have a significantly higher frequency of suicidal ideation, anxiety, and depression compared to healthy controls [32, 33].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In addition to anxiety, depression, and sleep disorders, patients with AD report higher rates of mental and physical disturbances, work absenteeism, and activity impairment compared to non-AD controls [31]. …”
Section: Clinical Presentationmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic inflammatory skin disease that affects approximately 15%–30% of children and 2%–10% of adults worldwide . In addition to eczematous lesions, intense pruritus and a high burden of disease in affected patients are associated with AD . AD has been shown to have a large impact on health‐related quality of life (QoL) in adults and children with AD and their caregivers, affecting social functioning, emotional well‐being and academic and occupational pursuits .…”
Section: Introductionmentioning
confidence: 99%